Integrating social protection strategies for improved impact: A comparative evaluation of cash transfers and index insurance in Kenya - Jensen, Nathaniel D.; Ikegami, Munenobu; Mude, Andrew G. (Springer, 2017)
Social protection programmes aim to use public funds to reduce poverty and vulnerability. Cash transfers have proven to be an effective social protection strategy in many contexts but are extremely expensive. Researchers have suggested that integrating multiple interventions could improve the efficiency of protection programmes, but there are few evidence-based recommendations on how to best implement such approaches. This study uses household-level panel data to estimate the marginal impacts of observed cash and index insurance transfers (subsidies) on household income in northern Kenya. Those estimates are used to simulate sample-level poverty indices as the outcome of a standard cash transfer programme and of a similar programme that reallocates a small portion of the budget as an insurance subsidy to the vulnerable. We find that the integrated programme reduces poverty to a greater degree than do cash transfers alone, highlighting the importance of protecting the vulnerable in addition to supporting the poorest.